An HIV-1 and HIV-2 cross-reactive cytotoxic T-cell epitope. - Nixon, D; Huet, S; Rothbard, J; Kieny, M; Delchambre, M; Thiriart, C; Rizza, C; Gotch, F; Mcmichael, A (1990)
The HLA-B27-restricted HIV gag cytotoxic T-lymphocyte (CTL) epitope, 265-279, is highly conserved amongst HIV-1 isolates, only one, HIV-1ELI, having a single amino acid substitution. Over the same region HIV-2 differs by five amino acids. As a broadly cross-protective AIDS vaccine should protect against infection from all isolates of HIV-1 and HIV-2, we tested CTL specific for the HIV-1 265-279 epitope with peptide analogues from HIV-1ELI, HIV-2 and two simian immunodeficiency virus (SIV) isolates, and with recombinant vaccinia viruses expressing the respective gag genes, to determine whether there was any cross-reactivity for this CTL epitope. CTL from the HIV-1-infected donor could recognize the HIV-1ELI peptide, the HIV-2 peptide and recombinant vaccinia virus-infected target and one of the two SIV peptide-treated targets. Epitopes that exhibit such cross-reactivity may be valuable in vaccine design.